Computational Physics : With Worked Out Examples in FORTRAN and MATLAB - Bestehorn, Michael (De Gruyter, 2018)
Drawing on examples from various areas of physics, this textbook introduces the reader to computer-based physics using Fortran® and Matlab®. It elucidates a broad palette of topics, including fundamental phenomena in classical and quantum mechanics, hydrodynamics and dynamical systems, as well as effects in field theories and macroscopic pattern formation described by (nonlinear) partial differential equations. A chapter on Monte Carlo methods is devoted to problems typically occurring in statistical physics. ContentsIntroduction Nonlinear maps Dynamical systems Ordinary differential equations I Ordinary differential equations II Partial differential equations I, basics Partial differential equations II, applications Monte Carlo methods (MC) Matrices and systems of linear equations Program library Solutions of the problems README and a short guide to FE-tools.- Resumé vydavatel
Keywords: matematická fyzika; fyzika; zpracování dat; mathematical physics; physics; data processing; elektronické knihy; učebnice; electronic books; textbooks